Tissue-characteristic forms of glyceraldehyde 3-phosphate dehydrogenase - Ressler, N. (1970)
Glyceraldehyde 3-phosphate dehydrogenase exists in two different forms in various human tissue preparations. One of them is exhibited, after starch-gel electrophoresis, by a rapidly migrating or `fast' band and the other by a `slow' band. The proportion of the total activity in each of the two forms is characteristic of the type of tissue. A particulate fraction, obtained after centrifugation of homogenates, inhibits the enzyme activity and tends to convert the slow band into a fast one. The conversion is reversible. The fast band can also be converted into the slow one by addition of NAD(+) or ADP, or by dialysis against saturated sodium chloride solution. Conversions occur with the purified enzyme as well as with crude homogenates. The relevance of these findings to previous investigations and to glycolytic control mechanisms are discussed.